O trabalho docente na educação infantil pública em Belo Horizonte - Mercia de Figueiredo Noronha Pinto (2009)
Recent studies have showed that the right to early education is closely related to faculty work, especially on what concerns work relationships and conditions of professionals working with the children. In this themes scope, this thesis carried out a study on public early education in Belo Horizonte, aiming to analyze the conditions in which faculty work is carried out in the Unidades Municipais de Educação Infantil (UMEIs) [Early Education Municipal Unities] and in municipal schools, and to verify which are the implications for faculty work of creating the early educator career. The landmark of this investigation is the implementation of the First School Program after Law no. 8.679/2003 was enacted, creating the UMEIs and the job of early educator. The research development took place through document analysis and field research in a UMEI and in a early education school. As data-gathering instruments, we used questionnaires, observation, semistructured interviews and focus groups. The analyses carried out on faculty work were based mainly on the following authors: Apple (1987), Ball (2002), Birgin (2000), Castel (1998), Contreras (2002), Enguita (1991), Fanfani (2005, 2006, 2007), Hargreaves (1994), Mancebo (2007), Oliveira (2002, 2003, 2004, 2005, 2006, 2007, 2008), Pochmann (1999), Santos (1989, 1992), and Tardif & Lessard (2005, 2008), among others. The results show that the expansion of public early education in Belo Horizonte city was made viable by creating a specific job with pay lower than that of teachers who work in the other stages of basic education. Thus, we verified there is a process intensifying and making precarious the faculty work conditions of the early educators in Belo Horizontes Municipal Education Network, since the early educator job was created and a pay was assigned to it, as well as the magnifying of the educators performance areas.